Edukasi Pengelolaan Potensi Desa Melalui Program Katalog Paket Wisata Desa Donomulyo - Dharomesz, Vonezyo Yupanzara (Jurnal Atma Inovasia, 2022)
Donomulyo Village, which is located in Kulon Progo Regency, has the potential to be managed as a tourist village because the village still preserves several cultures and arts. The manifestation of this preservation is that there are still various art associations formed by the local community. The arts associations in Donomulyo Village include dance arts associations, theater arts associations, and music arts associations. In addition to culture and art, Donomulyo Village also produces various kinds of traditional handicrafts and culinary products. This is evidenced by the existence of a traditional craft and culinary production site in Donomulyo Village. The potentials of Donomulyo Village need to be developed in order to attract tourists. The author offers the "Donomulyo Village Tour Package Catalog" program as an effort to develop the potential of Donomulyo Village. The existence of this program is expected to help provide an overview to the villagers about compiling various village potentials into a tour package. In addition, the program can be a means to preserve and introduce culture and arts, crafts, and traditional culinary delights in Donomulyo Village. In the end, the goal of tourism development is that the people in Donomulyo Village can receive economic and welfare benefits.